Evaluating major anthropogenic VOC emission sources in densely populated Vietnamese cities. (1st February 2023) - Dominutti, Pamela A.; Hopkins, James R.; Shaw, Marvin; Mills, Graham P.; Le, Hoang Anh; Huy, Duong Huu; Forster, Grant L.; Keita, Sekou; Hien, To Thi; Oram, David E.
Abstract: Volatile organic compounds (VOCs) play an important role in urban air pollution, both as primary pollutants and through their contribution to the formation of secondary pollutants, such as tropospheric ozone and secondary organic aerosols. In this study, more than 30 VOC species were continuously monitored in the two most populous cities in Vietnam, namely Ho Chi Minh City (HCMC, September-October 2018 and March 2019) and Hanoi (March 2019). In parallel with ambient VOC sampling, grab sampling was used to target the most prevalent regional-specific emission sources and estimate their emission factors (EFs). Emission ratios (ERs) obtained from ambient sampling were compared between Vietnamese cities and other cities across the globe. No significant differences were observed between HCMC and Hanoi, suggesting the presence of similar sources. Moreover, a good global agreement was obtained in the spatial comparison within a factor of 2, with greater ER for aromatics and pentanes obtained in the Vietnamese cities. The detailed analysis of sources included the evaluation of EF from passenger cars, buses, trucks, motorcycles, 3-wheeled motorcycles, waste burning, and coal-burning emissions. Our comparisons between ambient and near-source concentration profiles show that road transport sources are the main contributors to VOC concentrations in Vietnamese cities. VOC emissions were calculated from measured EF and consumption data available in Hanoi and compared with those estimated by a global emission inventory (EDGAR v4.3.2). The total VOC emissions from the road transport sector estimated by the inventory do not agree with those calculated from our observations which showed higher total emissions by a factor of 3. Furthermore, the inventory misrepresented the VOCs speciation, mainly for isoprene, monoterpenes, aromatics, and oxygenated compounds. Accounting for these differences in regional air quality models would lead to improved predictions of their impacts and help to prioritise pollution reduction strategies in the region. Graphical abstract: Image 1 Highlights: VOC emission ratios do not show substantial seasonal differences in Ho Chi Minh City. VOCs from road transport emissions are similar to ambient concentration profiles in Hanoi. Large differences in speciation are observed between observations and inventory estimations. Observed total VOC road transport emissions are 3 times higher than those estimated by the inventory.